ASSESSMENT AND MAPPING OF THE MUDFLOW PHENOMENA INTENSITY IN CHARYN STATE NATIONAL NATURAL PARK - Zhanerke M. SHARAPKHANOVA; Yuisya F. LYY; Kamshat B. YEGEMBERDIYEVA (Geo Journal of Tourism and Geosites)
The aim of the article is to present the results of assessing the occurrence intensity of mudflow phenomena in the territory of the Charyn State National Natural Park (SNNP). The assessment and mapping of mudflow phenomena was carried out using field methods, comparative analysis of field materials, and a cartographic method. Based on indicators such as lithological composition of rocks, vertical dissection, surface slope and vegetation the assessment using number score was carried out and map of the territory of the Charyn SNNP was created. Thus, areas of tourist and recreational activity are susceptible to a high degree of mudflow phenomena.